2015
DOI: 10.1002/mds.26381
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic advances in restless legs syndrome (RLS)

Abstract: Levodopa and dopamine agonists have been the main treatment for restless legs syndrome during the past decades. Although their efficacy has been well documented over the short term, long-term dopaminergic treatment is often complicated by augmentation, loss of efficacy, and other side effects. Recent large randomized controlled trials provide new evidence for the efficacy of high-potency opioids and α2δ ligands, and several post hoc analyses, meta-analyses, algorithms, and guidelines have been published, often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Symptomatic drug treatment includes dopaminergic medication (levodopa, dopamine agonists), α2δ ligands (gabapentin, pregabalin), and opioids and GABA-A receptor agonists. See Table 5 [94][95][96][97][98][99]. In the few available direct comparative studies (pramipexole versus dual-release levodopa, or gabapentin versus ropinirole), similar effects on RLS were observed [100,101].…”
Section: Sleep-related Movement Disordersmentioning
confidence: 86%
“…Symptomatic drug treatment includes dopaminergic medication (levodopa, dopamine agonists), α2δ ligands (gabapentin, pregabalin), and opioids and GABA-A receptor agonists. See Table 5 [94][95][96][97][98][99]. In the few available direct comparative studies (pramipexole versus dual-release levodopa, or gabapentin versus ropinirole), similar effects on RLS were observed [100,101].…”
Section: Sleep-related Movement Disordersmentioning
confidence: 86%
“…Previous PET studies have revealed abnormalities in the dopaminergic system, such as hypofunction of the mesolimbic and nigrostriatal dopaminergic pathways [ 85 , 86 ]. Treatment with L-Dopa or dopamine agonists significantly reduced unpleasant sensations, pain, and sensory dysfunction in patients with restless legs syndrome [ 87 ]. These positive results of the use of dopaminergic drugs support the hypothesis that dopaminergic impairment can contribute to the development of symptoms of restless legs syndrome.…”
Section: Administration Of Dopaminergic Drugsmentioning
confidence: 99%
“…Dopaminergic agonists are considered the gold standard treatment for RLS [5]. However, dopaminergic medications are associated with "augmentation," a phenomenon characterized by RLS symptoms that start earlier in the daytime, and ascend up the body, sometimes involving the arms and trunk [6]. Also, dopaminergic therapies are associated with impulse control disorders, such as punding, pathologic gambling, binge eating and hypersexuality [7].…”
Section: Introductionmentioning
confidence: 99%